The Canadian Press and the Great Irish Famine: The Famine as an Irish, Canadian & Imperial, Global Issue - Pauline COLLOMBIER-LAKEMAN (Cahiers du MIMMOC)
For the Irish who chose to emigrate during the Great Famine (1845-1851), Canada was a refuge that welcomed as much as 45% of the total Irish emigration in 1847. The following paper intends to study the Canadian press in order to show how Canadians reacted to the first significant potato crop losses in Ireland after the autumn of 1846 and how they responded to the mass arrivals of famine-stricken Irish poor in 1847. This study of the Canadian press will be used to assess the level of solidarity that existed at the time within the British Empire.